Performance evaluation of the compounding robot, APOTECAchemo, for injectable anticancer drugs in a Japanese hospital - Takuya Iwamoto; Takuya Morikawa; Miki Hioki; Hirofumi Sudo; Demis Paolucci; Masahiro Okuda (BMC, 2017)
Abstract Background The accuracy, safety and feasibility of, the compounding robot APOTECAchemo were evaluated in the clinical practice of Japan. Methods Accuracy and precision of robotic preparations by APOTECAchemo was evaluated in 20 preparations of fluorouracil (FU) and cyclophosphamide (CPA) infusions by four pharmacists. Environmental and product contaminations with FU and CPA were evaluated by wipe testing. Robotic performance was compared with manual preparation in a biological safety cabinet. The number of robotic products, total compounding time and total pre-reconstitution time of lyophilized drugs between January 1, 2014 to December 31, 2015 were investigated. Results Robotic preparation resulted more accurate and precise (mean absolute dose error and coefficient of variation were 0.83 and 1.04% for FU and 0.52 and 0.59% for CPA) than those of manual preparation (respective values were 1.20 and 1.46% for FU and 1.70 and 2.20% for CPA). Drug residue was not detected from any of the prepared infusion bags with the robotic preparation, whereas FU was detected in two of four analyzed infusion bags with manual preparation. Average total time to make single anticancer drug preparation (compounding plus reconstitution of lyophilized drugs) was 6.11 min in the second half of 2015. During the study period, the highest percentage of production covered by APOTECAchemo was 70.4% of the total inpatient pharmacy activity. Conclusion Robotic preparation using APOTECAchemo should give substantial advantages in drug compounding for accuracy and safety and was able to be successfully worked in Mie university hospital.